Tadpole of Proceratophrys mantiqueira (Anura: Odontophrynidae), with a Description of Its Internal Oral Features - Provete, Diogo B.; Guimaraes, Carla S.; Melo, Lilian S. O. [UNESP]; Rossa-Feres, Denise de C. [UNESP] (Amer Soc Ichthyologists & Herpetologists, 2017)
We describe the larval external morphology and internal oral features of Proceratophrys mantiqueira from its type locality and provide novel natural history information for adults. The tadpoles of P. mantiqueira (Stage 37) exhibit a depressed body with low tail fins, eyes positioned dorsally, and a ventral oral disc bordered by a single row of marginal papillae, with a wide gap on the anterior labium; a few submarginal papillae may be present. The labial tooth row formula is 2(2)/3(1). The shape and amount of papillae in the buccal floor, especially the infralabial and lingual papillae, can distinguish the tadpole of P. mantiqueira from other congeners. Our results add important new data about the larval morphology of this species and may help future studies on the intrageneric relationships of Proceratophrys.